Formulation And Invitro Release Study Of Zidovudine Sustained Release Tablets - Deepika, V (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The purpose of the present investigation was to out to formulate sustained release matrix tablets of zidovudine. The sustained release matrix tablets were prepared by wet granulation method by using hydrophilic polymers like HPMC, SCMC and Na Alginate (F1 to F9).A total of nine formulations were prepared using hydrophilic polymers. The formulation F3 was selected for further modification using different hydrophobic polymers as granulating agents, such as PVP, Eudragit RL100 and Ethylcellulose to control the drug release. The hydrophilic matrix of HPMC alone could not control the Zidovudine release effectively for 12 hours. The formulations F10 to F15 released more than 95% of AZT at the end of 12 hours. The drug polymer interaction was investigated by FTIR studies. Zidovudine tablets were evaluated for various physical tests like weight variation, hardness, friability and results showed they comply with in the limits. Kinetic treatment to the in vitro release data revealed that the drug release followed first order release and mechanism of drug release is by Non-fickian transport. Of all formulations, F15 is the most successful and cost-effective formulation among the matrix tablets developed in the present study.